Gambaran Ketidakpuasan Tubuh pada Remaja Putri Kelas VIII di SMP Negeri 2 Sragen - Natasya Odelia; Sri Ernawati; Anniez Rachmawati Musslifah (Universitas Maritim AMNI Semarang, 2025)
Individuals who assume that their physical condition is not the same as their ideal body concept, then the individual will feel physically lacking, this condition causes the individual to be unable to accept their condition as it is so that they can experience body dissatisfaction. The purpose of this study was to determine the picture of body dissatisfaction in adolescent girls. This study used qualitative method with 4 female adolescents in grade VIII at SMP Negeri 2 Sragen. The results of this study were 75% of students felt less confident and less satisfied with their body shape and 25% of students felt satisfied with their body shape because they had an athletic and good body, students also explained that they liked their healthy body which made them able to play volleyball well and win championships.